PENDAMPINGAN PEMBUATAN NOMOR INDUK BERUSAHA (NIB) SEBAGAI UPAYA PENINGKATAN LEGALITAS UMKM “CELLO CAKE & BAKERY” DI KELURAHAN BENOWO, SURABAYA - Prasetyo Pambudhi, Kukuh; Dermawan, Rizky (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Business Identification Number (NIB) is the identity of a business actor, whether business entity, individual business or business entity, which is issued by Online Single Submission (OSS). Meanwhile, the micro and small business permit, hereinafter abbreviated as (IUMK), is a one-sheet letter in the form of a micro-small business permit. This has not yet been applied to the "Cello Cake & Bakery" MSME. This Village Development Program is carried out in the Surabaya City Area, specifically in Benowo Village. And carried out at the UMKM "Cello Cake & Bakery". The result of this activity is to increase knowledge for UMKM regarding the legality of a business by creating a Business Identification Number through OSS, and the main objective is to issue a Business Identification Number certificate for UMKM Cello Cake & Bakery. This can also help UMKM players increase their knowledge for future business development.